JURNAL SEJARAH HUKUM - Abd Thalib; Abel Alwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Legal history is a branch of study that examines the evolution of law over time and the factors influencing changes in a society's legal system. This research aims to analyze the historical development and formation of the Indonesian legal system, spanning the colonial period, independence, the Old Order, the New Order, and the Reform Era. The study employs a normative-juridical method with historical and conceptual approaches, utilizing a literature review of legislation, books, and scholarly journals. The findings indicate that the Indonesian legal system is an amalgamation of various legal systems: customary law (*adat*), Islamic law, and the Continental European legal system inherited from the Dutch. Following independence, national legal development focused on decolonizing the law, with Pancasila and the 1945 Constitution serving as the primary foundations. The evolution of Indonesian law has been shaped by the political and social dynamics of each governing era. During the Reform Era, the legal system underwent reform through amendments to the 1945 Constitution and the establishment of various independent institutions designed to strengthen the rule of law and democracy. Consequently, an understanding of legal history is essential for building a national legal system that is responsive, equitable, and aligned with societal developments.